Powerful switch based on CX1525A thyratron - Chertishev, I.A.; Ivakhnenko, M.V.; Kaplij, D.A.; Khomyakov, E.A.; Kosoi, A.I.; Titov, V.Yu.; Tur, Yu.D.; Tsymbal, V.A.; Zajtsev, E.I.; Zajtsev, I.N. (Вопросы атомной науки и техники, 2014)
Thyratrons of obsolete types TGI1-2500/50, TGI1-2500/35, TGI1-5000/50 are used in modulators of NSC KIPT of as a switch, their service life has expired. To update the modulator we selected thyratron СХ1525А of company EЕV, which technical parameters met the requirements: switched current 2.3 kA, anode voltage up to 40 kV, pulse frequency up to 300 Hz, pulse duration 5 μs. Thyratron switchboard based on СХ1525А was de-signed and constructed. The results of study the switch operation in mode of active accelerator are reported.